A series of uranium (IV, V, VI) tritylimido complexes, their molecular and electronic structures and reactivity with CO2. - Schmidt, Anna-Corina; Heinemann, Frank Wilhelm; Maron, Laurent; Meyer, Karsten (Inorganic Chemistry, 2014)
A series of uranium tritylimido complexes with structural continuity across complexes in different oxidation states, namely U(IV), U(V), and U(VI), is reported. This series was successfully synthesized by employing the trivalent uranium precursor, [(((nP,Me)ArO)3tacn)U(III)] (1) (where ((nP,Me)ArO)3tacn(3-) = trianion of 1,4,7-tris(2-hydroxy-5-methyl-3-neopentylbenzyl)-1,4,7-triazacyclononane), with the organic azides Me3SiN3, Me3SnN3, and Ph3CN3 (tritylazide). While the reaction with Me3SiN3 yields an inseparable mixture of both the azido and imido uranium complexes, applying the heavier Sn homologue yields the bis-μ-azido complex [(((nP,Me)ArO)3tacn)U(IV)2(μ-N3)2] (2) exclusively. In contrast to this one-electron redox chemistry, the reaction of precursor 1 with tritylazide solely leads to the two-electron oxidized U(V) imido [(((nP,Me)ArO)3tacn)U(V)(N-CPh3)] (3). Oxidation and reduction of 3 yield the corresponding U(VI) and U(IV) complexes [(((nP,Me)ArO)3tacn)U(VI)(N-CPh3)][B(C6F5)4] (4) and K[(((nP,Me)ArO)3tacn)U(IV)(N-CPh3)] (5), respectively. In addition, the U(V) imido 3 engages in a H atom abstraction reaction with toluene to yield the closely related amido complex [(((nP,Me)ArO)3tacn)U(IV)(N(H)-CPh3)] (6). Complex 6 and the three tritylimido complexes 3, 4, and 5, with oxidation states ranging from +IV to +VI and homologous core structures, were investigated by X-ray diffraction analyses and magnetochemical and spectroscopic studies as well as density functional theory (DFT) computational analysis. The series of structurally very similar imido complexes provides a unique opportunity to study electronic properties and to probe the uranium imido reactivity solely as a function of electron count of the metal-imido entity. Evidence for the U-N bond covalency and f-orbital participation in complexes 3-6 was drawn from the in-depth and comparative DFT study. The reactivity of the imido and amido complexes with CO2 was probed, and conclusions about the influence of the formal oxidation state are reported.